Economic thought in Spain : selected essays - Grice-Hutchinson, Marjorie (E. Elgar, 1993)
The book presents in one volume the most important papers of Dr Grice-Hutchinson. It presents a fuller explanation than has hitherto been available of her argument that a 'Salamancan School' in the 16th century pioneered a utility and scarcity approach in value theory that led naturally, if not logically, to a rich statement of the quantity theory of money well in advance of other writers such as Bodin.